HUBUNGAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI KLINIK VICTORY TELUKDALAM KABUPATEN NIAS SELATAN - Hasibuan, Indri Yani (Universitas Nias Raya, 2024)
This research aims to determine the relationship between work motivation and employee performance at the Victory Telukdalam Clinic, South Nias Regency. This type of research is a type of quantitative correlational research. The type of data used is quantitative data and the data source was obtained through distributing questionnaires to employees at the Victory Clinic. The sampling technique used was a non-probability sampling technique with a saturated sampling method, so the population in this study was all employees at the Victory Teluk Dalam clinic and the sample used in this research was all employees at the Victory Teluk Dalam clinic, totaling 31 people. The analytical method used in this research is simple linear regression analysis. The results of this research indicate that there is a relationship between work motivation and employee performance at the Victory Telukdalam clinic, South Nias Regency.